1999
DOI: 10.1139/cjm-45-10-826
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an urban effluent on the bacterial community structure in the Arga River (Spain), with special reference to culturable Gram-negative rods

Abstract: The Arga River is an interesting system in which to study the impact of urban effluent pollution because it receives a single effluent in the form of wastewater discharge from the city of Pamplona. To analyze the extent of this discharge, total bacteria, culturable heterotrophic bacteria, and Gram-negative heterotrophic bacteria were enumerated and 409 isolates of the latter were identified. One sampling station was located upstream from the inflow, while five were located up to 30 km downstream. Bacterial cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…These recorded values of FC and A. hydrophila fall within the range of those previously published for highly polluted rivers and streams that in most cases were subjected to wastewater discharge from sewage treatment systems (Monfort and Baleux 1991;Goñi-Urriza et al 1999;Jugnia and Nsimé-Ngando 2001;Griesel and Jagals 2002). Thus, waters from the Mfoundi River watershed can presumably be considered unsuitable for their multiple primary uses by the near shore population.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These recorded values of FC and A. hydrophila fall within the range of those previously published for highly polluted rivers and streams that in most cases were subjected to wastewater discharge from sewage treatment systems (Monfort and Baleux 1991;Goñi-Urriza et al 1999;Jugnia and Nsimé-Ngando 2001;Griesel and Jagals 2002). Thus, waters from the Mfoundi River watershed can presumably be considered unsuitable for their multiple primary uses by the near shore population.…”
Section: Resultssupporting
confidence: 84%
“…The next challenge will be to determine, among other parameters, the physico-chemical factors affecting the observed spatial distribution. Moreover, following the study by Goñi-Urriza et al (1999), the extent to which the presence and density of A. hydrophila may be used as an indicator of river pollution, and whether the represent a health hazard to the users of these waters, are questions to be addressed by further microbiological investigation and epidemiological surveys.…”
Section: Resultsmentioning
confidence: 99%
“…As opposed to everywhere else, this variation was evident at both low (phylum) and high (OTU) levels of resolution. The bacteria we found associated with the change are indicators of wastewater [44, 45], and probably derived from a treatment plant (MC Stiles Plant), that discharges into the Mississippi River north of downtown Memphis. The influence of anthropogenic inputs at this site is confirmed by a recently published finding that in these samples were elevated concentrations of wastewater contaminants including pharmaceuticals and personal care products [46].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have documented the potential ecosystem effects of WWTP effluent, including increased nutrient loading (Waiser et al, 2011) and eutrophication (Gücker et al, 2006). Several previous studies have also examined the effects of WWTP effluent on bacterial populations within the water column (Cébron et al, 2004;Garnier, et al, 1992;Goñi-Urriza et al, 1999) and some have demonstrated the ability of microorganisms contained in the effluent to persist in the water column of the receiving system (Cébron et al, 2004).…”
Section: Urbanization and Freshwater Ecosystemsmentioning
confidence: 99%
“…Numerous studies have documented the potential ecosystem effects of WWTP effluent, including increased nutrient loading (Waiser et al, 2011) and eutrophication (Gücker et al, 2006). Several previous studies have also examined the effects of WWTP effluent on bacterial populations within the water column (Cébron et al, 2004;Garnier et al, 1992;Goñi-Urriza et al, 1999) and some have demonstrated the ability of microorganisms contained in the effluent to persist in the water column of the receiving system (Cébron et al, 2004). However, few studies have examined the potential effects of WWTP effluent on benthic microbial communities (Wakelin et al, 2008) despite the fact that (1) bacterial numbers are generally much higher in freshwater sediment that in the overlying water (Sander and Kalff, 1993) and (2) that benthic microbial communities are critical components of lotic ecosystems, as they contribute to organic matter decomposition, nutrient cycling, and bioremediation of a variety of pollutants.…”
Section: Introductionmentioning
confidence: 99%